Local relief approximation with deterministic methods for optimizing production facilities layout on rough terrain - V. G. Khomchenko; I. M. Zuga; A. N. Kuzhel; A. O. Stroyev (Омский научный вестник)
Relief approximation is proposed in the vicinity of the facility location at the current computational iteration using the Lagrange’s interpolating polynomial. Formulas are given for the operative transport at each coordinates iteration of a proportional geodetic grid in the local coordinates of 16 fixed points required during the optimization process. Localization of the relief vicinity is performed algorithmically depending on the current values of the geometric image center coordinates of the certain facility foundation. Via an example of a real territory relief the comparative assessment of the accepted local approximation with the results of the software product AutoCad Civil 3D is given.